Problems in Determining Customer Official Income in Fund Distribution and Financing Installment Payments Based on Aceh Qanun Number 11 of 2018 Concerning Islamic Financial Institutions - Sari Husmaijar; Hasballah Thaib; Utary Maharany Barus; Idha Aprilyana Sembiring (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Aceh government has ratified Qanun Aceh number 10 of 2018 concerning Islamic Financial Institutions, the content of which is an order against all financial institutions, both banks and non-banks, must operate in accordance with sharia principles. Article 14 paragraphs and (6) states that financing distributed by Islamic banks prioritizes profit-sharing-based contracts and also pays attention to the abilities and needs of customers, the ability and needs of customers must pay attention to: financing applications from prospective customers based on the needs, business / business prospects of prospective customers who meet the criteria for banking financing eligibility. This type of research is Normative Law research. The results showed that the principle in determining official income is the application of the 5C principle (character, capacity, capital, collateral, condition of economy) as a guideline for Islamic banks in making decisions on whether customers are worthy or not to receive financing from banks. The application of the principle of official customer income in the distribution of funds and payment of financing installments is carried out by looking at the ability and ability of customers from how much income.